PENGARUH BELANJA PEMERINTAH, INFLASI, NILAI TUKAR, EKSPOR, DAN PENANAMAN MODAL ASING TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Atsa, Hawa Nabila; Diandra Aulia, Agna; Athaya Tiyar, Rakha; Zahra, Hanatul; Kafi, Muhammad; Amalia Ramadhani, Naila; Amalia, Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the short-run and long-run effects of government spending, inflation, exchange rate, exports, and foreign direct investment (FDI) on Indonesia's economic growth over the period 1995-2024. Using the Autoregressive Distributed Lag (ARDL) approach and Error Correction Model (ECM) with annual time-series data from the World Bank, the study finds that government spending and FDI positively and significantly affect economic growth in the long run, while the exchange rate exerts a significant negative effect. Inflation and exports show statistically insignificant effects in the long run. In the short run, government spending has a positive immediate impact but a negative lagged effect, suggesting a crowding-out mechanism. The exchange rate consistently depresses growth in both lag periods. The ECM coefficient of -0.91 confirms that 91% of short-run disequilibrium is corrected within one year. Dummy variables for the 1997-1998 Asian Financial Crisis and the 2020 COVID-19 pandemic are included to control for structural shocks.